(untitled) (Biodiversitas Journal of Biological Diversity, 2018)
Falah S, Sari NM, Hidayat A. 2018. Decolorization of Remazol Brilliant Blue R by laccase of newly isolated Leiotrametes flavida Strain ZUL62 from Bangka Heath Forest, Indonesia. Biodiversitas 19: 633-639. The use of microbial enzymes seems to be an appropriate approach to neutralize synthetic dyes, providing an eco-friendly and cost-competitive alternative solution for treating industrial effluents. The objective of this research was to select the most potential fungal isolate with high laccase activity to decolorize Remazol Brilliant Blue R (RBBR) synthetic dyes. The isolation of fungal body and sampling of wood decay specimens were conducted in six different locations in heath (kerangas) forest of Bangka Belitung, Indonesia. In the present study, a total of 13 isolates were screened by using indicator plate method and for their enzyme activity. The preliminary screening was done to screen ligninolytic fungi. Then the primary screening using various indicator compounds was conducted to select laccases-producing fungi. The enzyme activity assay was performed to select fungal isolate with the highest activity. We found that the most potential fungi belonged to Leiotrametes flavida Strain ZUL62, which had been confirmed by molecular identification using 5.8S rDNA/ITS analysis. In addition, the laccase from Leiotrametes flavida Strain ZUL62 could decolorize RBBR, exhibiting a high rate of decolorization rate of 62% without any mediator within 24 h of incubation. To our best of knowledge, this study represented the first report about Leiotrametes flavida Strain ZUL62 and its potential laccase enzyme for dyes effluent treatment.